2004
DOI: 10.1177/039463200401700305
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Grade Procedure for Generation of mRNA Transfected Dendritic Cells from Purified Frozen CD34+ Blood Progenitor Cells

Abstract: Enriched CD34+ peripheral blood progenitor cells (PBPC) are frequently used as stem cell support in cancer patients following high dose therapy. Since precursor dendritic cells (DCs) originate from haematopoietic progenitor cells, purified CD34+ cells might also serve as starting cells for ex-vivo production of DC. In the present study we developed a clinical grade procedure for ex-vivo production of DC derived from enriched CD34+ cells. Different concentrations of CD34+ cells were grown in gas-permeable Teflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Moreover, dental pulp is a viable source of easily attainable cells with a possible potential for cell transplantation therapies, indicating the presence of a cell population in the dental pulp with neuronal differentiation capacity (21), and also having the ability to differentiate in mesenchymal tissue, after induction, offering a novel approach for regenerative medicine (22)(23)(24). These results are in accordance with the existence in the adult organism of a biological niche of the mesenchymal stem cells that are not only restricted to bone marrow but are present in different tissues and, under defined inductive conditions, are able to acquire characteristics of cells derived from embryonic mesoderm, as well as possessing ectodermal and neuronal properties (25)(26)(27). In this paper, apart from cytofluorimetric determination, we report the isolation and characterization, by morphological analysis, of a homogeneous mesenchymal stem cells population expanded ex vivo from dental pulp and their ability to grow in the presence of biomaterials.…”
Section: Resultssupporting
confidence: 60%
“…Moreover, dental pulp is a viable source of easily attainable cells with a possible potential for cell transplantation therapies, indicating the presence of a cell population in the dental pulp with neuronal differentiation capacity (21), and also having the ability to differentiate in mesenchymal tissue, after induction, offering a novel approach for regenerative medicine (22)(23)(24). These results are in accordance with the existence in the adult organism of a biological niche of the mesenchymal stem cells that are not only restricted to bone marrow but are present in different tissues and, under defined inductive conditions, are able to acquire characteristics of cells derived from embryonic mesoderm, as well as possessing ectodermal and neuronal properties (25)(26)(27). In this paper, apart from cytofluorimetric determination, we report the isolation and characterization, by morphological analysis, of a homogeneous mesenchymal stem cells population expanded ex vivo from dental pulp and their ability to grow in the presence of biomaterials.…”
Section: Resultssupporting
confidence: 60%
“…Although satisfactory and clinically applicable cryopreservation methods for DCs have been described [18][19][20][21], methods to cryopreserve products transduced with Adv vectors have been little studied [22]. In most clinical trials reported to date, DCs were freshly prepared for each administration either from fresh blood [23][24][25][26][27], leukapheresis products [23,28,29], or from frozen aliquots of PBMCs obtained by leukapheresis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cell types frequently used as starting material for DC vaccine manufacturing are monocytes (Anguille et al, 2012c) and CD34 + hematopoietic progenitor cells derived from bone marrow (Lardon et al, 1997), peripheral blood (Mu et al, 2004), or cord blood (Chen et al, 2013). Monocyte-derived DCs (moDCs) are by far the most commonly used DC type in DC vaccine formulations Chiang et al, 2015).…”
Section: B Pharmacological Aspects Of Dendritic Cell-based Cancer Immentioning
confidence: 99%